2015
DOI: 10.1007/s00127-015-1050-1
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the income and suicidality relationship: income rank is more strongly associated with suicidal thoughts and attempts than income

Abstract: Connor, R. C. (2015) Explaining the income and suicidality relationship: income rank is more strongly associated with suicidal thoughts and attempts than income. Social Psychiatry and Psychiatric Epidemiology, 50(6) and sex by education by region). Along with absolute income and demographic covariates, these variables were tested for associations with suicidal thoughts and attempts, both across the lifetime and in the past year.Results. Absolute income was associated with suicidal thoughts and attempts, both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
32
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 40 publications
7
32
0
1
Order By: Relevance
“…This parallels findings with mental health and depressive symptoms as the outcome (Elgar et al, 2013;Hounkpatin et al, 2015;Wetherall, Daly, Robb, Wood, & O'Connor, 2015;Wood, Boyce, et al, 2012) as well findings from a study by Subramanyam et al (2009) which indicated that percentile income rank significantly predicted self-rated health in a US population after controlling for actual income. The income rank specification is consistent with the psychosocial hypothesis but differs from the Yitzhaki Index in that it proposes that health is not necessarily related to the magnitude of the difference, but rather the position of income on the income distribution within a comparison group.…”
Section: Introductionsupporting
confidence: 79%
“…This parallels findings with mental health and depressive symptoms as the outcome (Elgar et al, 2013;Hounkpatin et al, 2015;Wetherall, Daly, Robb, Wood, & O'Connor, 2015;Wood, Boyce, et al, 2012) as well findings from a study by Subramanyam et al (2009) which indicated that percentile income rank significantly predicted self-rated health in a US population after controlling for actual income. The income rank specification is consistent with the psychosocial hypothesis but differs from the Yitzhaki Index in that it proposes that health is not necessarily related to the magnitude of the difference, but rather the position of income on the income distribution within a comparison group.…”
Section: Introductionsupporting
confidence: 79%
“…A growing body of evidence reports that low rank is associated with higher psychological distress (Wood, Boyce, et al, 2012) and depressive symptoms (Hounkpatin et al, 2015) and a higher likelihood of suicidal thoughts and suicide attempts (Wetherall et al, 2015), independent of absolute income. Moreover, associations between income rank and allostatic load strengthen the pathway between rank, stress and psychological distress, strongly suggesting that income rank relates to health (Daly, Boyce and Wood, 2015).…”
Section: Characteristics Of Income and Status Comparisonsmentioning
confidence: 99%
“…Moreover, associations between income rank and allostatic load strengthen the pathway between rank, stress and psychological distress, strongly suggesting that income rank relates to health (Daly, Boyce and Wood, 2015). These studies do however have methodological limitations: suicidal thoughts and attempts were restricted to cross-sectional analyses (Wetherall et al, 2015) and the longitudinal analyses (Wood, Boyce, et al, 2012;Hounkpatin et al, 2015) did not control for unobserved variance, introducing the possibility that unobserved variance influenced their results. In the current study, examining the comparative strength of income rank and distance from the mean determines whether people are more sensitive to income rank -implicating an evolutionary explanation for the negative association between income and psychological distress -or whether the magnitude of income differences (distance from the mean) is more relevant to psychological distress.…”
Section: Characteristics Of Income and Status Comparisonsmentioning
confidence: 99%
See 2 more Smart Citations